Pengaruh Kualitas Sumber Daya Manusia dan Kualitas Anggaran Terhadap Kinerja Keuangan Daerah Yang Dimoderasi Dengan SIMDA Pada SKPD Kabupaten Buton Utara - Riawan Riawan (Universitas Negeri Malang, 2016)
This study was conducted to examine the influence of human resources quality and budget quality on local government financial performance. In addition, this study was conducted to examine the influence of moderating variables Regional Management Information System on the relationship between human resources quality and budeget quality on local government financial performance. The number of population in the study are all the regional work units (SKPD) in North Buton Regency with totaling 34. The sampling using census techniques throughout the regional work units (SKPD) in North Buton Regency used a sample. Of the 34 questionnaires distributed, only 32 work units (SKPD) who returned the questionnaires. To test hypothesis using multiple linear regression analysis with the application program partial least square (PLS). The results showed that (1) Human resources quality have a positive significant effect on local government financial performance, (2) Budget quality have a positive significant effect on local government financial performance, (3) Regional Management Information System (SIMDA) have a positive significant effect in moderating the influence of human resources quality on local government financial performance, (4) Regional Management Information System (SIMDA) have a positive significant effect in moderating the influence of budget quality on local government financial performance. Keywords: Human Resources Quality, Budget Quality, Regional Management Information System and Local Government Financial Performance